First-attack pediatric hypertensive crisis presenting to the pediatric emergency department - Yang Wen-Chieh; Zhao Lu-Lu; Chen Chun-Yu; Wu Yung-Kang; Chang Yu-Jun; Wu Han-Ping (BMC Pediatrics, 2012)
Background Hypertensive crisis in children is a relatively rare condition presenting with elevated blood pressure (BP) and related symptoms, and it is potentially life-threatening. The aim of this study was to survey children with first attacks of hypertensive crisis arriving at the emergency department (ED), and to determine the related parameters that predicted the severity of hypertensive crisis in children by age group. Methods This was a retrospective study conducted from 2000 to 2007 in pediatric patients aged 18 years and younger with a diagnosis of hypertensive crisis at the ED. All patients were divided into four age groups (infants, preschool age, elementary school age, and adolescents), and two severity groups (hypertensive urgency and hypertensive emergency). BP levels, etiology, severity, and clinical manifestations were analyzed by age group and compared between the hypertensive emergency and hypertensive urgency groups. Results The mean systolic/diastolic BP in the hypertensive crisis patients was 161/102 mmHg. The major causes of hypertensive crisis were essential hypertension, renal disorders and endocrine/metabolic disorders. Half of all patients had a single underlying cause, and 8 had a combination of underlying causes. Headache was the most common symptom (54.5%), followed by dizziness (45.5%), nausea/vomiting (36.4%) and chest pain (29.1%). A family history of hypertension was a significant predictive factor for the older patients with hypertensive crisis. Clinical manifestations and severity showed a positive correlation with age. In contrast to diastolic BP, systolic BP showed a significant trend in the older children. Conclusions Primary clinicians should pay attention to the pediatric patients who present with elevated blood pressure and related clinical hypertensive symptoms, especially headache, nausea/vomiting, and altered consciousness which may indicate that appropriate and immediate antihypertensive medications are necessary to prevent further damage.